Alterations in zebrafish development induced by simvastatin: Comprehensive morphological and physiological study, focusing on muscle. Issue 17 (November 2016) - Campos, Laise M; Rios, Eduardo A; Guapyassu, Livia; Midlej, Victor; Atella, Georgia C; Herculano-Houzel, Suzana; Benchimol, Marlene; Mermelstein, Claudia; Costa, Manoel L
The cholesterol synthesis inhibitor simvastatin, which is used to treat cardiovascular diseases, has severe collateral effects. We decided to comprehensively study the effects of simvastatin in zebrafish development and in myogenesis, because zebrafish has been used as a model to human diseases, due to its handling easiness, the optical clarity of its embryos, and the availability of physiological and structural methodologies. Furthermore, muscle is an important target of the drug. We used several simvastatin concentrations at different zebrafish developmental stages and studied survival rate, morphology, and physiology of the embryos. Our results show that high levels of simvastatin induce structural damage whereas low doses induce minor structural changes, impaired movements, and reduced heart beating. Morphological alterations include changes in embryo and somite size and septa shape. Physiological changes include movement reduction and slower heartbeat. These effects could be reversed by the addition of exogenous cholesterol. Moreover, we quantified the total cell number during zebrafish development and demonstrated a large reduction in cell number after statin treatment. Since we could classify the alterations induced by simvastatin in three distinct phenotypes, we speculate that simvastatin acts through more than one mechanism and could affect both cell replication and/or cell death and muscle function. Our data can contribute to the understanding of the molecular and cellular basis of the mechanisms of action of simvastatin.